MYXOEDEMA MADNESS: WHEN HYPOTHYROIDISM TURNS PSYCHOTIC - Yahaya , Nurul Syamimi; Borhan , Marisa Khatijah (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Myxoedema madness is a rare but serious neuropsychiatric manifestation of severe hypothyroidism. We report a case of overt hypothyroidism following radioactive iodine (RAI) therapy, presenting with paradoxical psychotic symptoms. CASE A 43-year-old Malay male with underlying ischemic heart disease, severe mitral regurgitation, and toxic multinodular goiter (MNG) was admitted for acute behavioral changes. Diagnosed with toxic MNG in 2019, he was initially treated with carbimazole before undergoing his first RAI therapy in January 2024. He reported mood swings that improved after starting carbimazole, not needing psychiatric evaluation. A second RAI therapy was administered in January 2025 after failed first therapy. Two months post- RAI therapy, his thyroid function test (TFT) showed a TSH of 7.6 mIU/L and a free T4 of 7.8 pmol/L; hence, carbimazole 2.5 mg daily was withheld, and he was scheduled for follow-up. One month after stopping carbimazole, he presented to the Emergency Department with a five-day history of disorganized behavior, irrelevant speech, and bizarre ideations. Clinically, he was restless, requiring physical restraint. There were no signs of meningism or hypothyroidism. His inflammatory markers and brain CT were normal, and both urine drug toxicology and infective screening were negative. A repeat TFT confirmed overt hypothyroidism post-RAI therapy (TSH >49.9 mIU/L, free T4 3.9 pmol/L) and levothyroxine 50 mcg daily was started. He was also started on risperidone by the psychiatric team for acute delirium secondary to hypothyroidism. Following treatment, he became calmer and more manageable. CONCLUSION Myxoedema madness has been reported in patients with untreated or inadequately treated hypothyroidism, particularly post-thyroidectomy or RAI therapy, and in patients with psychiatric comorbidities. Symptoms such as hallucinations, delusions, and disorganized behavior are typically reversible with appropriate treatment, including thyroid hormone replacement. Clinicians should maintain vigilance for myxoedema madness in hypothyroid patients presenting with acute behavioral changes.